Developing Self-Learning in Four Skills Courses: Students' Perception Using Undiksha Moodle E-learning During Covid-19 Outbreak - Luh Maytri Lindayani; I.G.A Lokita Purnamika Utami; Nyoman Karina Wedhanti (Universitas Majalengka, 2021)
This study aims to identify students' perception of the Undiksha Moodle E-learning Platform's strengths and weaknesses in four skills courses. This research is qualitative research supported by quantitative data. A case study was used in this study to identify the phenomenon and describe it in detail. The subject of this study was English Language Education students who took the subject into four skills courses. In total, there were 12 students involved in the study. This investigation's object is students' perception of the Undiksha Moodle E-learning platform's weaknesses and strengths in four skills courses. Data collection is conducted with questionnaires and semi-structured interview guide to see the results' suitability with implementation in the field. Thus, the data that has been obtained analyzed descriptively quantitatively and qualitatively. This study showed that students have a positive perception of developing self-learning using the Undiksha Moodle E-learning Platform to feel the platform's strength. However, students expressed that the Undiksha Moodle E-learning Platform's weakness, which is yet not significant. The results are seen from the data that states that students are neutral on Undiksha Moodle E-learning's weakness.